PENGARUH BIAYA PRODUKSI TERHADAP PENJUALAN PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI TAHUN 2021-2023 - Fauziyanti, Wachidah; Annafia, Layla Asti Aisya (Sekolah Tinggi Ilmu Ekonomi Semarang, 2025)
This study aims to analyze the influence of raw material costs, labor costs, and overhead costs on sales in food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The research employs a quantitative approach using multiple linear regression analysis. The data used are secondary data derived from company financial reports over a three-year period. The results show that raw material costs and labor costs do not have a significant effect on sales, whereas overhead costs have a significant and positive impact. The regression model shows an Adjusted R Square value of 0.936, indicating that 93.6% of the variation in sales can be explained by the three independent variables. The study concludes that effective management of overhead costs can contribute to increased sales performance.